Experimental Analysis on Fatigue Life Assessment of Dissimilar Aluminum Alloys Weld Joints under Four-Point Rotating Bending Condition - Muhammad Hashir; Tauseef-ur Rehman; Praveen Kanti; Muhammad Yasar Javaid; Cheol-Woo Park (Applied Sciences, 2022)
Industrial applications often require welded joints of dissimilar metals to perform reliably under adverse working conditions. Such conditions demand high resistance to failure modes, such as fatigue, corrosion, and creep. In applications involving intense vibrational and cyclic loading conditions, high strength-to-weight ratio metals, including aluminum, are more vulnerable to fatigue failure. This study investigates the fatigue strength of base metals and tungsten inert gas welded joints of the two most widely used aluminum alloys, AA7075 and AA2024, under four-point rotating bending. For the comparative study, these dissimilar alloys were joined together by using two different filler rods, AA4047 and AA4043, under similar welding conditions. SN curves for all the samples were generated through the experimental iterations. A comparison of different results shows that welded samples have better fatigue strength than the base metals, while, as a filler, AA4047 has better resistance to fatigue fracture than AA4043.